Difficulties faced by second language learners of Arabic when translating Tamil sentences into Arabic - Mohammed Sainulabdeen Zunoomy; Mohammed Cassim Sithy Shathifa (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2021)
The Muslims around the world use Arabic language for many functions. Likewise, Sri Lankan Muslims also use it in their daily worships and School & University studies although they speak Tamil as a native language. According to this, the Learners of Arabic language as a foreign language face difficulties and make mistakes in identifying meanings of sentences and translating them into Arabic language. Therefore, this research aims to identify errors and difficulties faced by Arabic language learners when translating them. This research is based on: descriptive and analytical methodology. Primary data were gathered from interview and questionnaire. Interview was conducted with specialized students of second year from the department of Arabic language, Faculty of Islamic Studies and Arabic Language, South Eastern University of Sri Lanka and questionnaires were distributed to one hundred male and female general degree students of second year from the department of Arabic language. The sample of the study was chosen randomly among them. Secondary data were collected from books, research papers, articles, thesis and websites. MS Excel was used for data analysis. This research found that the Learners of Arabic language as a foreign language faced difficulties when translating in choosing appropriate words and determining their meaning. They also made mistakes in identifying subject, object, masculine and feminine, articles, adjective, genitive and in using appropriate conjunctions and prepositions.